The analgesic efficiency of combined pregabalin and ketamine for total hip arthroplasty: a randomised, double‐blind, controlled study. (January 2014) - Martinez, V.; Cymerman, A.; Ben Ammar, S.; Fiaud, J. F.; Rapon, C.; Poindessous, F.; Judet, T.; Chauvin, M.; Bouhassira, D.; Sessler, D.; Mazoit, X.; Fletcher, D.
Summary Ketamine and pregabalin each provide postoperative analgesia, although the combination has yet to be evaluated. One hundred and forty‐two patients undergoing total hip arthroplasty were randomly assigned to receive ketamine alone, pregabalin alone, ketamine and pregabalin combined, or placebo. Pain scores at rest and on movement, morphine consumption, side‐effects, pressure pain thresholds and secondary hyperalgesia were evaluated. Mean (SD) total 48‐h morphine use was reduced in patients given ketamine alone (52 (22) mg) and pregabalin alone (44 (20) mg) compared with placebo (77 (36) mg) p < 0.001. Morphine use was further reduced in patients given both ketamine and pregabalin (38 (19) mg) with an interaction between ketamine and pregabalin (ANOVA factorial; p = 0.028). Secondary hyperalgesia was reduced by ketamine. There were no differences between groups in pain scores after surgery, pressure pain thresholds or side‐effects. The combination of pregabalin and ketamine has a small, beneficial clinical effect.